Prevalence of Salmonella in raw and cooked foods in Malaysia - Arumugaswamy, R.K.; Rusul, G.; Abdul Hamid, S.N.; Cheah, C.T. (Academic Press Limited, 1995)
A total of 331 food samples consisting of 219 raw and 112 ready-to-eat cooked foods were examined for the presence of Salmonella. Thirty-two percent of the raw foods and 17% of the ready-to-eat cooked foods examined contained the pathogen. Among the raw foods, high proportions of chicken pieces (39%), liver (35%) and gizzard (44%) were contaminated with Salmonella. Salmonella serotypes were also isolated from dried oysters (86%), prawns (25%), oriental shrimp paste (belacan) containing more than 15% NaCl (11%), beef (8%), leafy vegetables (4%) and bean sprouts (20%). Fourteen percent of the ready-to-eat foods (cooked chicken, beef and prawns) obtained from street vendors were positive. The extent of Salmonella detected in uncooked (66%) and ready-to-eat satay (23%) is of significance. Satay is a popular food in Asian countries; however the presence of Salmonella in satay has not been documented. Salmonella isolated from test foods belong to 20 different serovars. The predominant serovars were S. blockley, S. enteritidis, S. chinicol, S. muenchen and S. agona. Salmonella serovars detected from dried oysters (S. bareilly and S. singapore) fermented sucrose.